Konfliktdynamiken – Kriegsdynamiken: Zur Konstitution und Eskalation innergesellschaftlicher Konflikte - Mayer, Lotta (transcript, 2019)
War as a genuinely social phenomenon: Lotta Mayer reconstructs the dynamic processes of intra-societal conflicts and wars on the basis of Symbolic Interactionism.